A Study of the Effect of Inflation and Exchange Rate on Stock Market Returns in Ghana - Charles Kwofie; Richard Kwame Ansah (International Journal of Mathematics and Mathematical Sciences)
The study examined the effect of exchange rate and inflation on stock market returns in Ghana using monthly inflation and exchange rate data obtained from the Bank of Ghana and monthly market returns computed from the GSE all-share index from January 2000 to December 2013. The autoregressive distributed lag (ARDL) cointegration technique and the error correction parametization of the ARDL model were used for examining this effect. The ARDL and its corresponding error correction model were used in establishing the long- and short-run relationship between the Ghana Stock Exchange (GSE) market returns, inflation, and exchange rate. The result of the study showed that there exists a significant long-run relationship between GSE market returns and inflation. However, no significant short-run relationship between them existed. The result also showed a significant long- and short-run relationship between GSE market returns and exchange rate. The variables were tested for long memory and it was observed that such property did exist in these variables, making it a desirable feature of which investors can take advantage of. This is due to the establishment of long-run effect of inflation and exchange rate on stock market returns.